2009
DOI: 10.2353/ajpath.2009.080966
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Cell Cycle Control in Cultured Endometrial Cells from Patients with Endometriosis Harboring the Progesterone Receptor Polymorphism PROGINS

Abstract: Presently, little is understood about how endometriosis is established or maintained, or how genetic factors can predispose women to the disease. Because of the crucial role that the progesterone receptor polymorphism PROGINS plays in predisposing women to the development of endometriosis, we hypothesized that this variant may influence critical steps during endometrial cell metabolism that are involved in the pathogenesis of endometriosis. Eutopic endometria were collected from three sources: women with endom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 62 publications
1
16
0
2
Order By: Relevance
“…Previous studies developed by our group showed that endometrial cells exhibit higher proliferation rates when compared to controls [24]. We [40] and others researchers [41,42] also demonstrated that patients with endometriosis have reduced p27 kip1 expression in eutopic endometrium and/or endometriotic lesions when compared to the controls, suggesting that p27 kip1 gene expression alteration may be involved in the deregulation of cell cycle mechanisms in endometriotic tissues.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Previous studies developed by our group showed that endometrial cells exhibit higher proliferation rates when compared to controls [24]. We [40] and others researchers [41,42] also demonstrated that patients with endometriosis have reduced p27 kip1 expression in eutopic endometrium and/or endometriotic lesions when compared to the controls, suggesting that p27 kip1 gene expression alteration may be involved in the deregulation of cell cycle mechanisms in endometriotic tissues.…”
Section: Discussionsupporting
confidence: 50%
“…Adherent stromal cells were grown in phenol-free Dulbecco's Modified Eagle's Medium (Sigma-Aldrich, St. Louis, MO) containing 10 % heat-inactivated fetal bovine serum (Life Technologies, Inc., Rockville, MD), 100 IU/mL penicillin, 100 mg/mL streptomycin (Sigma-Aldrich, St. Louis, MO), and 250 mg/mL amphotericin-B (Cultilab, Campinas, Brazil) in a humidified incubator at 37°C with 5 % CO 2 . The typical yield of stromal cells using this technique is 90 % as previously established by our group [24].…”
Section: Primary Endometrial Cell Culturementioning
confidence: 93%
“…Recent clinical and experimental evidences have indeed suggested that epigenetic defects in the sperm DNA is associated with recurrent spontaneous abortions [4,31]. Since the PR mRNA is expressed in the mature spermatozoa [37,38] and the PROGINS polymorphism is associated with defective PR transcription [11,33], we tested if the PROGINS insertion in the paternal genome has any effect on fertilization, embryo quality and pregnancy rates. However, no significant differences were noted when these parameters were compared in the group, where the male partner had PROGINS allele vs the wild type allele.…”
Section: Discussionmentioning
confidence: 99%
“…The Alu element reportedly reduces the stability of the PROGINS transcript compared with the wild allele; the amino acid substitution V600L leads to differences in PR phosphorylation and degradation upon ligand binding, most likely as a result of differences in the three-dimensional structures of the variant [33]. As a consequence, the PROGINS variant displays decreased transactivation activity, the resulting protein has poor bioactivity and affects cell cycle in cultured endometrial cells [11,33]. Intriguingly, studies have demonstrated that the presence of this polymorphism increases the risk of women towards gynecologic disorders including cancers [30,32,34,39].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the ALU insertion of PROGINS haplotype results in a reduction of gene transcript and the missense Val600Leu leads to different PGR phosphorylation and degradation on ligand binding (Romano et al, 2007). Consequently, the subjects carrying the PROGINS polymorphism show a reduced progesterone responsiveness due to the decreased receptor bioactivity (Romano et al, 2007;D'Amora et al, 2009).…”
Section: Fig 1 (A)mentioning
confidence: 99%